1997
DOI: 10.1152/jn.1997.77.4.2153
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization and Behavioral Correlation of Changes in Regional Cerebral Blood Flow With Classical Conditioning of the Human Eyeblink Response

Abstract: Laterality of changes in regional cerebral blood flow (rCBF) during classical conditioning of the human eyeblink response was studied and changes in rCBF were correlated with conditioned responses. In 10 normal volunteers, rCBF was mapped with positron emission tomography and H2(15)O during pairings of a binaural tone conditioned stimulus and an air puff unconditioned stimulus to the left eye. Control conditions consisted of explicitly unpaired presentations of the tone and air puff before (control) and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
99
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 35 publications
17
99
1
Order By: Relevance
“…While these ideas are speculative, the lack of N100 and P200 learning-related associations could reflect the possibility that auditory cortex is not necessary for normal CR acquisition in humans. However, it should be noted that several functional imaging studies in humans have in fact shown auditory cortical activity for paired trials during EBC (Molchan, Sunderland, McIntosh, Herscovitch, & Schreurs, 1994;Schreurs et al, 1997; but see Ramnani, Toni, Josephs, Ashburner, & Passingham, 2000, for an exception). Further work will be necessary to determine the specific role (if any) of the sensory cortex during delay EBC in humans.…”
Section: Discussionmentioning
confidence: 99%
“…While these ideas are speculative, the lack of N100 and P200 learning-related associations could reflect the possibility that auditory cortex is not necessary for normal CR acquisition in humans. However, it should be noted that several functional imaging studies in humans have in fact shown auditory cortical activity for paired trials during EBC (Molchan, Sunderland, McIntosh, Herscovitch, & Schreurs, 1994;Schreurs et al, 1997; but see Ramnani, Toni, Josephs, Ashburner, & Passingham, 2000, for an exception). Further work will be necessary to determine the specific role (if any) of the sensory cortex during delay EBC in humans.…”
Section: Discussionmentioning
confidence: 99%
“…[Insert Figure 2 here] Second, we used seed PLS to assess functional connectivity, understood as the network of areas whose activity statistically correlates with activity in a seed region or regions (i.e., a seed voxel) across the task conditions (Della-Maggiore et al, 2000;McIntosh, 1999;McIntosh et al, 1997;Schreurs et al, 1997). Seed PLS analysis is almost identical to task PLS analysis.…”
Section: Partial Least Squares (Pls) Analysismentioning
confidence: 99%
“…For the purposes of the current review, we will narrow our focus to functional imaging studies that have examined classical conditioning by using adequate control conditions. Classical conditioning in humans has centered on paradigms such as eyelid, jaw, and limb movement conditioning, and fear conditioning (Molchan et al, 1994;Hugdahl et al, 1995;Logan and Grafton, 1995;Blaxton et al, 1996;Timmann et al, 1996;Schreurs et al, 1997bSchreurs et al, , 2001Hugdahl, 1998;LaBar et al, 1998;Knight et al, 1999;Buchel and Dolan, 2000;Fischer et al, 2000;Maschke et al, 2000).…”
Section: Human Studiesmentioning
confidence: 99%